2021
DOI: 10.1101/2021.05.07.443174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fibrinogen αC-subregions critically contribute blood clot fibre growth, mechanical stability and resistance to fibrinolysis

Abstract: Fibrinogen is essential for blood coagulation. The C-terminus of the fibrinogen α-chain (αC-region) is composed of an αC-domain and αC-connector. Two recombinant fibrinogen variants (α390 and α220) were produced to investigate the role of subregions in modulating clot stability and resistance to lysis. The α390 variant, truncated before the αC-domain, produced clots with a denser structure and thinner fibres. In contrast, the α220 variant, truncated at the start of the αC-connector, produced clots that were po… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, bulk measurements show that fibers are not completely straight but straightened by up to 25% shear strain of the whole clot, and fibers only start to align in the direction of stress above 25% shear strain. 54,57 Fibers appear less straight on electron microscopy images than confocal microscopy 29 and fibers appear less straight in uncrosslinked clots. 30 Strain stiffening is a typical behavior of filamentous biological polymers 58 and involves complex interplay of entropic and enthalpic elasticity: low strain mechanical behavior is dominated by entropic behavior, when thermal undulations are pulled out decreasing the degree of disorder, the entropy, 58 while enthalpic behavior dominates at high strains when the filament backbone is stretched leading to actual bonds being pulled, thus increasing enthalpy, the internal energy.…”
Section: Fibrin Extensibility and Strain Stiffeningmentioning
confidence: 99%
See 1 more Smart Citation
“…However, bulk measurements show that fibers are not completely straight but straightened by up to 25% shear strain of the whole clot, and fibers only start to align in the direction of stress above 25% shear strain. 54,57 Fibers appear less straight on electron microscopy images than confocal microscopy 29 and fibers appear less straight in uncrosslinked clots. 30 Strain stiffening is a typical behavior of filamentous biological polymers 58 and involves complex interplay of entropic and enthalpic elasticity: low strain mechanical behavior is dominated by entropic behavior, when thermal undulations are pulled out decreasing the degree of disorder, the entropy, 58 while enthalpic behavior dominates at high strains when the filament backbone is stretched leading to actual bonds being pulled, thus increasing enthalpy, the internal energy.…”
Section: Fibrin Extensibility and Strain Stiffeningmentioning
confidence: 99%
“…21 A recent study from our lab found that the absence of the αC-domain (α390 truncation) leads to thinner, highly branched fibers resulting in reduced clot firmness, whereas abolishing the complete αC-region including the globular domain and the connector region (α220 truncation) impairs longitudinal growth of protofibrils and results in clots with even lower firmness and a highly abnormal network structure with stunted fibers and a severely reduced resistance to fibrinolysis. 29 Thus, besides the kinetic effect on fibrin assembly and lateral aggregation, the αC-region has important roles in clot formation including longitudinal fibrin fiber growth and clot stability.…”
Section: Bonds In Fibrinmentioning
confidence: 99%